2011
DOI: 10.1134/s1070428011110029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of epothilone D with the forced application of oxycyclopropane intermediates

Abstract: The total synthesis of epothilone D with six-fold application in the intermediate stages of successive cyclopropanation -opening or cleavage of the three-membered ring was performed. These transformations underlie the new stereoselective method developed for coupling fragments С 7 -С 12 and С 13 -С 21 in the target molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…382 There has been a number of total syntheses that have used the oxidative cleavage strategy to form synthetic intermediates (Scheme 187). In this general strategy, treatment of a cyclopropyl alcohol (892) with PhI(OAc) 2 in the presence of either an alcoholic solvent or water will generate the relevant carboxylic acid derivative (893) (Scheme 187a), with ethylene 390 The formations of carboxylic acid 897, an intermediate for the synthesis of epothilone D, 391,392 and carboxylic acid 898, an intermediate for the synthesis of capsaicin, have been reported by Kulinkovich and coworkers. 393 Other applications of this reaction include an intermediate for the synthesis of the C13−C21 fragment of epithilones reported by Kulinkovich and co-workers, 394 and an intermediate for the synthesis of Unit A of the cryptophycins reported by Shklyaruck.…”
Section: Oxidative Ring Opening Using Hypervalent Iodine Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…382 There has been a number of total syntheses that have used the oxidative cleavage strategy to form synthetic intermediates (Scheme 187). In this general strategy, treatment of a cyclopropyl alcohol (892) with PhI(OAc) 2 in the presence of either an alcoholic solvent or water will generate the relevant carboxylic acid derivative (893) (Scheme 187a), with ethylene 390 The formations of carboxylic acid 897, an intermediate for the synthesis of epothilone D, 391,392 and carboxylic acid 898, an intermediate for the synthesis of capsaicin, have been reported by Kulinkovich and coworkers. 393 Other applications of this reaction include an intermediate for the synthesis of the C13−C21 fragment of epithilones reported by Kulinkovich and co-workers, 394 and an intermediate for the synthesis of Unit A of the cryptophycins reported by Shklyaruck.…”
Section: Oxidative Ring Opening Using Hypervalent Iodine Reagentsmentioning
confidence: 99%
“…The authors reported that both cyclopropyl mesylates and tosylates work in this protocol, and the scope of the Lewis acid includes MgBr 2 , MgCl 2 , AlCl 3 , and TiCl 4 . This methodology has found repeated use in the early steps of several natural products syntheses, such as epothilone A, (+)-neopeltolide, neolaulimalide, amphidinolides B1, and their corresponding building blocks (Scheme b). …”
Section: Acid-mediated Ring Opening Of Cyclopropyl Alcoholsmentioning
confidence: 99%
“…By taking advantage of the ring-opening or ring fragmentation reactions of cyclopropanol intermediates, a total synthesis of epothilone D 339 has been completed with 1.6% overall yield starting from (R)-methyl 2,3-O-isopropylideneglycerate. 225,226 To mimic the binding pose assigned to the previously reported EpoA-microtubule binding model, a series of conformationally restrained epothilone analogues with a short bridge between the methyl groups at C6 and C8 have been synthesized and evaluated. 227 Bioassay against A2780 human ovarian cancer and PC3 prostate cancer cell lines indicated the introduction of a bridge between C6-C8 led to a decreased potency by 25-1000 fold in comparison with natural epothilone D. A stereoselective strategy has been devised for the synthesis of 12,13-cyclopropylepothilone B 348 and its heterocycle-modied side chain variants.…”
Section: Phytoalexinsmentioning
confidence: 99%
“…Also in 2009, Kulinkovich et al 61 carried out the synthesis of both enantiomers of the C13-C21 thiazole fragment of epothilone using a different cyclopropanol approach. They initially In 2011, Kulinkovich and Hurski 62 reported the synthesis of epothilone D 105 using several Kulinkovich cyclopropanation reactions throughout the synthesis followed by various ring opening transformations. Although the synthetic strategy required several reactions to effect formation and transformation of the cyclopropanol intermediates, the relatively low costs of the reagents and the chemical diversity of the cyclopropanol unit together with its simple formation make this an attractive route for the synthesis of these macrocycles.…”
Section: Synthesis Of Natural Productsmentioning
confidence: 99%